How Does Product Competitiveness Mediate the Effect of Business Legality and Halal Labelling on MSME Income? - Didi Sukardi; Moh. Mabruri Faozi; Abdul Ghoni; Dwi Ayu Maharani; Sri Najmi Aprilia; Windy Nurditasari; Muhammad bin Jasmi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
MSMEs have a very important role as one of the pillars of national economic income, for that it is very important for MSME actors to ensure the legality of their business so that they can access financial facilities from banks and financial institutions. The certainty of products to have halal certification is a necessity considering the target population in Muslim-majority Indonesia. This study aims to measure and analyze how much influence legality and halal labels have on MSME income by using product advantages as mediation variables. This study used quantitative methods. Data analysis uses multiple linear regression analysis, path analysis, and partial tests. The results of the partial test (t-test) showed that the legality of the halal labeling business and product competitiveness had a positive and significant effect on the income of MSMEs in the Bhinangkit Community, while the coefficient of determination (R2) test showed that the influence of business legality, halal labeling, and product competitiveness on MSME income was 89.7%. The path analysis shows that business legality and the inclusion of halal labels have no effect on MSME income mediated by by-product competitiveness with a calculated t value of 0.2496 for business legality and 0.0344 for halal label marking.